High-entropy-doping effect in a rapid-charging Nb2O5 lithium-ion battery negative electrode - Junling Xu; Fuqiang Xie; Lipeng Huang; Nana Li; Shang Peng; Wensheng Ma; Kai Zhang; Yanxue Wu; Lianyi Shao; Xiaoyan Shi; Jizhang Chen; Li Tao; et al. (Nature Communications)
Abstract Doping is an important approach to tailor materials’ properties, yet the success of doping can depend on factors such as ionic radii similarities. For materials like silicon or perovskite, doping is not only facile to implement but can also enhance material properties. However, for host lattice structures like Nb2O5, doping without causing phase change is challenging. Here, we introduce a high-entropy-doping effect in Nb2O5. Unlike traditional doping approaches, high-entropy-doping minimizes the chemical properties of doping elements and focuses solely on their quantities. By high-entropizing the doping elements (selecting 10–15 from Mg, Ca, Sr, Ba, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, In, Sn, Sb, Y, Mo, La, Ce) and keeping them within a certain range of doping concentrations (1–3 mol%), a successful high-entropy-doping is achieved for Nb2O5 without phase change. The obtained high-entropy-doped (HED) Nb2O5 exhibits rapid-charging capabilities. At a rate of 40 A g−1, the HED-Nb2O5 delivers a capacity of 80 mAh g−1, whereas the undoped Nb2O5 fails to exceed 25 mAh g−1.